HUBUNGAN KUALITAS TIDUR DENGAN PRESTASI BELAJAR REMAJA DI PONDOK PESANTREN MANBA’UL HIKAM PUTAT TANGULANGGIN SIDOARJO - Nafi’a, Fikrotul Ilman; Firiyah, Erna Tsalatsatul; Sari, Ika Puspita (LPPM STIKes Bahrul Ulum Jombang, 2020)
Sleep is a basic need for everyone. Sleep quality is said to be good if it does not show signs of sleep deficiency, such as swelling in the eyelids, and dark areas around the eyes. Many sleep conditions are found among teenagers who can later cause many effects, such as reduced learning concentration, memory, thinking and health disorders. The purpose of this research is to know the relationship between sleep quality with adolescent learning achievements. The research uses the collation analytic design with the cross-sectional retrospective approach. Samples used as much as 60 respondents. The sampling technique used is purposive sampling. Data collection using questionnaires and report value. The results of the study gained good sleep quality with good learning achievement as many as 11 respondents (18.3%), while poor sleep quality with good learning achievement as many as 45 respondents (75.0%). Based on the statistical test there is a value of rs = 0.000 with P = 1,000 where p > 0.05 so that HI rejected means there is no relationship the quality of sleep and learning performance of young women at Manba'ul Hikam Boarding School Putat Tanggulangin Sidoarjo. Counseling guidance is required and motivates students to be more active in learning.